The Implementation of MUI’s Fatwa Number 12 of 2009 Concerning Halal Slaughter Certification Standard in West Java - Muhammad, Bohari Agus; Yani, Ahmad; Suryadi, Rudi Ahmad; Jubaedah, Dedah; Maulin, Mery (TEMALI : Jurnal Pembangunan Sosial, 2023)
The background of research was the stunning phenomenon of a captive bolt that can injure animals. This was not following the MUI Fatwa Number 12 of 2009 concerning Halal Slaughter Certification Standards. This study aimed to analyze the standard of halal slaughtering according to the MUI fatwa Number 12 of 2009, the MUI istinbat method in determining the MUI fatwa, the implementation of the MUIâ€™s Fatwa at Slaughterhouses in West Java. The types of research were qualitative with empirical juridical. The method was analytic descriptive. Data collection techniques used observation, interview, and documentation. The literature analysis was carried out in depth on the MUI Fatwa, the opinions of scholars, and other relevant sources. This analysis was to strengthen the juridical aspect of halal slaughter. The research conclusions were first, the MUI fatwa followed its systematics, which referred to the Al-Qur'an, hadith, and the opinions of scholars and veterinary science, especially on stunning. Second, the MUI istinbÄá¹ method were bayani related to the Al-Qur'an, hadith, and the opinions of scholars, taâ€™lili related to al-hayah al-mustaqirrah and stunning, and istislahi associated with mentioning the name of Allah in the slaughtering process. Third, implementing the fatwa at the slaughterhouses in West Java generally did not comply with the Shari'a slaughtering process, including many slaughtering treatments that did not follow the fatwa, especially stunning on the captive bolt.